RANTAI PASOKAN GLOBAL DAN NASIONALISME SUMBER DAYA ALAM: KAJIAN TERKAIT HILIRISASI NIKEL DI INDONESIA - Barizi, Muhammad Hirza; Triarda, Reza (Indonesian Association for International Relations, 2023)
This research explains the progress of Indonesia’s nickel down streaming despite in climate of resource nationalism. The concepts of global supply chain and hybrid resource nationalism are applied using descriptive qualitative methods with literature-based research as data collection. The research found that convergence between global business and the Indonesian government’s interest creates a favourable condition for the progress of nickel downstream. Global businesses are trying to diversify from the domination of the Chinese electric vehicle supply chain and Indonesia has become the ideal alternative. On the other hand, the Indonesian government needs foreign investment to sustain its resource nationalism project. As a result, resource nationalism that emerges in the nickel sector is moderate and not against foreign participation while foreign companies and governments are looking for new locations to lower the dependence on China. The combination of the two situations forms the main argument of this research as to how Indonesia’s nickel down streaming has been sustained